The Assistance of Sukosari Bandongan Elementary School Teachers through STEM Education as a Provision for Learning Innovation - Chasanah, Aprilia Nurul; Wicaksono, Arief Budi; Darmawan, Ericka; Ardiyanto, Bagas; Abdulloh, Maryam (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. This community service program is encouraged by the need for partners, which is the absence of specific activities related to the development of science and technology. Therefore, through the introduction of STEM (science, technology, engineering, and mathematics) in the learning, it is expected that this program can provide a lighter for the Sukosari Bandongan Elementary School teachers. STEM forms quality human resources to reason, think critically, logically, and systematically so that later they can be useful in facing global challenges and solving problems in everyday life. Purpose. This program aims to provide teachers with learning innovations through STEM education. Method. The activity consists of training in making simple products from the surrounding environment which can later be used as learning media. The training is carried out using lecture, discussion, practice, and mentoring methods. Results. The expected output is an increase in basic knowledge, especially in the field of science and technology which is manifested in simple STEM-based products. There are also some other products like training modules, posters, and publications of service results on social media. Conclusion. STEM education is a form of assistance to Sukosari elementary school teachers in improving learning innovation. The teachers need assistance to explore learning materials that can be integrated with STEM. They have very good motivation in practicing simple STEM-based tools. This can be seen from those who actively participate in the training sessions, practice properly, and ask some questions about some matters they do not yet clearly understand. The created simple products can be simple demonstration examples in a STEM-nuanced learning.